(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT This study aims to describe how the performance management of the people’s service program for land certificates (LARASITA) by the Land Office of Aesesa District, Nagekeo Regency. This research uses a qualitative approach with a descriptive type. The data collection technique is done by interview and documentation. Meanwhile, the selection of informants was used by purposive sampling technique. From this research, the LARASITA program performance management through the team is quite optimal. Especially in good scheduling, the team members are according to the needs in the field and the services provided by the team are quite satisfying to the community even though there are still many obstacles that the team still faces. The biggest obstacles faced were networks, hilly roads, and the most visible socialization. Keywords: Performance management, LARASITA Program, Service Innovation